Modeling urban tree growth as a part of the green infrastructure to estimate ecosystem services in urban planning - Fauk, Tino; Schneider, Petra (Frontiers in Environmental Science, 2023)
Trees play a basic role in urban green infrastructure (UGI) due to their role for delivering ecosystem services. Having in view the function of trees in the long term greenery planning, it is fundamental to understand their growth processes and impacts. The contribution applied statistical methods in order to assess the allometric functions of urban trees. Allometry is about measuring and comparing relationships between body size and how it relates to a wide variety of biological variables. The database used was the tree cadastre of the city of Magdeburg, Germany, containing information for the period from 1834 to 2021. The tree cadastre Magdeburg (as of 06/2022) contains 89,766 individual trees. The tree species and genus Acer campestre, A. platanoides, Malus spp. and Quercus robur were used for the investigation. The results of the multiple of regression show, that the years after planting for the tree species have Acer campestre and A. platanoides mostly a significance relationship between the parameters and the years after planting, which is not the case for Malus spp. and Quercus robur.